2014
DOI: 10.3390/nano4010175
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite Nanoparticles Induce Genotoxicity in the Lungs of Mice via Inflammatory Response

Abstract: Nanomaterials are useful for their characteristic properties and are commonly used in various fields. Nanosized-magnetite (MGT) is widely utilized in medicinal and industrial fields, whereas their toxicological properties are not well documented. A safety assessment is thus urgently required for MGT, and genotoxicity is one of the most serious concerns. In the present study, we examined genotoxic effects of MGT using mice and revealed that DNA damage analyzed by a comet assay in the lungs of imprinting control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 37 publications
(45 reference statements)
1
38
0
Order By: Relevance
“…However, nitric oxide is produced by activated macrophages in inflamed organs in vivo. In the in vivo toxicity tests of ENM, macrophage phagocytosing test substances are frequently observed . Similarly, MWNT‐7 was phagocytosed by RAW264.7 in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, nitric oxide is produced by activated macrophages in inflamed organs in vivo. In the in vivo toxicity tests of ENM, macrophage phagocytosing test substances are frequently observed . Similarly, MWNT‐7 was phagocytosed by RAW264.7 in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…However, recently, large and global efforts have been made to assess and manage the risks of ENM. It has been pointed out that ENM may come to possess their biological functions, including toxicity, by the different modes of action from overscaled counterparts, and that inflammatory response by virtue of immune cells, such as macrophages, and oxidative stress and signaling agents, such as cytokines, play major roles in the mechanism underlying effects of ENM on tissue resident cells . In Kato et al (2017) we revealed that the interaction between tissue resident cells and immune cells is important for the genotoxic mechanisms of nanomaterials.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…An increase in MN frequency was also detected in bone marrow cells of mice intraperitoneally exposed to magnetite nanoparticles [104], or after intravenous administration of polyaspartic acid-coated ION (magnetite) [105]. Totsuka et al [115] examined genotoxic effects of magnetite nanoparticles in mice intratracheally instilled, obtaining significant increases in DNA adduct levels, oxidative stress and DNA breaks in treated animals as compared with controls. In addition, inflammatory cell infiltration and focal granulomatous formations were also observed in lungs of exposed mice, suggesting that an inflammatory response might be involved in genotoxicity induced by ION in mice lungs [116].…”
Section: Genotoxicitymentioning
confidence: 99%